2019
DOI: 10.18257/raccefyn.799
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary characterization of the dominant baroclinic modes of a tropical Andean reservoir during a dry period

Abstract: A partir de datos de campo y un modelo numérico simple, se investigaron las ondas internas   escala de cuenco en un embalse tropical andino durante un período seco. La estructura y el período de las oscilaciones baroclínicas observadas, se infirieron a partir del análisis espectral de las series de temperatura medidas y de los desplazamientos verticales de las isotermas asociadas. El modo de oscilación dominante identificado a partir de los datos de campo constaba de dos capas que oscilaban con velocidades ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…The above implicitly suggests that this normal mode could be regarded as the canonical resonant response of stratified basins to wind [1]. After Mortimer's work, several studies have reported wind-induced resonant regimes in lakes [1,7,[10][11][12][13][14][15][16]. However, these observations show that the first vertical seiche (V1H1) is not the only one susceptible to wind-driven amplification.…”
Section: Discussion and Summarymentioning
confidence: 96%
See 2 more Smart Citations
“…The above implicitly suggests that this normal mode could be regarded as the canonical resonant response of stratified basins to wind [1]. After Mortimer's work, several studies have reported wind-induced resonant regimes in lakes [1,7,[10][11][12][13][14][15][16]. However, these observations show that the first vertical seiche (V1H1) is not the only one susceptible to wind-driven amplification.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…As a result, an oscillation mode with a frequency close to the forcing frequency [5][6][7][8] is overamplified relative to the rest of the modes that the system admits. Observations in lakes show that basin-scale internal waves, commonly called internal seiches [9], are susceptible to resonating with diurnal winds [1,7,[10][11][12][13][14][15][16]. Examples of these modes of motions are the first vertical, first horizontal mode, V1H1 [ Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This vertically transported heat and that added by the plume produced a thick metalimnion, indicating that the inflows have two effects on the dry season stratification: (1) to incorporate heat directly at intermediate layers and (2) mix heat downward from the surface layer to conform the thick metalimnion. Diapycnal mixing by basin‐scale internal waves is negligible in Porce II according to the near molecular eddy vertical diffusivity (Román‐Botero et al 2017; Posada‐Bedoya et al 2019), and signatures of nonlinear waves and their associated mixing were not identified, nor in measurements or the model, so mixing below the surface layer was dominated by the river plume. The metalimnion thickening by the plume in Porce II differs from the river‐induced mixing reported in other systems where the inflow entered directly at the surface mixed layer and deepened it (Carmack et al 1979; Fenocchi et al 2017; Xie et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant basin‐scale baroclinic motions of the lake are confined to the 6 km closest to the dam, as the upstream part of the reservoir is too shallow (Fig. 1b) due to sedimentation (Posada‐Bedoya et al 2019), so in this work we refer to baroclinic modes in the main basin (Fig. 1b) and do not consider possible oscillations over the delta.…”
Section: Methodsmentioning
confidence: 99%